Antibacterial properties of a modified magnesium alloy in vitro with clinical strains of non-fermentative gram-negative microorganisms - Chornyi, V. M.; Чорний, Владислав Вадимович; Черный, В. Н. (Запорізький державний медичний університет, 2020)
The aim. To determine the antibacterial effect of the products of biodegradation of magnesium alloy ML-10 on the clinical strains of Pseudomonas aeruginosa and Acinetobacter baumannii and, based on the results, substantiate the possibility of this alloy using in orthopedic and traumatological practice as implants with antibacterial activity. Materials and methods. Magnesium alloy extract was prepared on the basis of Mueller-Hinton broth (pH 7.4). The clinical strains of A. baumannii (15) and P. aeruginosa (15) were used in sensitivity testing. The bacteriostatic activity of the alloy extract was estimated by the visual growth presence or absence in test-tubes with microorganisms; bactericidal activity – by the growth of microbial colonies presence or absence on plates with Mueller-Hinton agar after culturing from test tubes for 24, 28 and 72 hours. Results of the study showed that the extract of magnesium alloy ML-10 has a high bacteriostatic and bactericidal activity against the clinical strains of A. baumannii and P. aeruginosa. In test tubes with an extract, the growth of microorganisms was not visually detected, which indicates a significant bacteriostatic activity of the magnesium alloy biodegradation products. The study of bactericidal activity found that the maximum growth of bacteria on agar was observed only after the first culturing from the test tubes (the extract incubation for 24 hours) in which the microorganisms were added in a concentration of 109, 108, 107 CFU/ml the day before. The number of colonies growing on agar after the second culturing (the extract incubation for 48 hours) significantly decreased in the process of thermostating, and after the third culturing (the extract incubation for 72 hours) the microorganism growth was absent on a dense medium in most experiments. High bactericidal activity of the magnesium alloy was found in the experiments with the extract containing 106, 105, 104 CFU/ml. The growth of colonies was absent on the dense medium after culturing from these tubes during the entire experiment. Conclusions. The products of magnesium alloy ML-10 biodegradation have shown high bactericidal activity against the non-fermentative gram-negative microorganisms A. baumannii and P. aeruginosa. Мета роботи – визначити антибактеріальну активність продуктів біодеградації магнієвого сплаву МЛ-10 щодо клінічних штамів Acinetobacter baumannii та Pseudomonas aeruginosa й на підставі результатів, що отримали, обґрунтувати можливість його використання в ортопедії, травматології як імплантатів, що мають антибактеріальну активність. Матеріали та методи. Використали екстракт магнієвого сплаву МЛ-10, що приготували на основі бульйону Мюллера– Хінтона (рН 7,4), а також 15 штамів A. baumannii та 15 штамів P. aeruginosa. Бактеріостатичні властивості оцінювали за наявністю або відсутністю візуального зростання мікроорганізмів у пробірках з екстрактом, бактерицидні – за наявністю або відсутністю зростання колоній цих мікроорганізмів на агарі Мюллера–Хінтона після висіву з екстракту. Результати. Досліджуваний екстракт магнієвого сплаву МЛ-10 має високу бактеріостатичну та бактерицидну активність щодо клінічних штамів A. baumannii та P. aeruginosa. У дослідних пробірках зростання мікроорганізмів візуально не виявили, що свідчить про чималу бактеріостатичну активність. Вивчаючи бактерицидну активність, виявили: максимальне зростання бактерій на агарі спостерігали тільки після першого висіву (24 годин інкубації) з пробірок, в які напередодні додали мікроорганізми в концентрації 109, 108, 107 КУО/мл. З часом термостатування кількість колоній, що виростала на агарі після другого висіву (48 годин інкубації екстракту), значущо зменшувалася, а після третього висіву (72 години інкубації екстракту) – здебільшого зростання мікроорганізмів відсутнє. Висока бактерицидна активність продуктів біодеградації сплаву виявлена в дослідах з екстрактом, де в ємності напередодні додали 106, 105, 104 КУО/мл, – зростання колоній на щільному середовищі після висіву з цих пробірок відсутнє протягом усього експерименту. Висновки. Продукти біодеградації магнієвого сплаву МЛ-10 мають високу бактерицидну активність щодо клінічних штамів неферментуючих грамнегативних мікроорганізмів, як-от A. baumannii, P. aeruginosa. Цель работы – определить антибактериальную активность продуктов биодеградации магниевого сплава МЛ-10 по отношению к клиническим штаммам Acinetobacter baumannii и Pseudomonas aeruginosa и на основании полученных результатов обосновать возможность его использования в ортопедии и травматологии в качестве имплантатов, обладающих антибактериальной активностью. Материалы и методы. В работе использовали экстракт магниевого сплава МЛ-10, приготовленный на основе бульона Мюллера–Хинтона (рН 7,4), а также 15 штаммов A. baumannii и 15 штаммов P. aeruginosa. Бактериостатические свойства оценивали по наличию или отсутствию визуального роста микроорганизмов в пробирках с экстрактом, бактерицидные – по наличию или отсутствию роста колоний данных микроорганизмов на агаре Мюллера–Хинтона после высева из экстракта. Результаты. Исследуемый экстракт магниевого сплава МЛ-10 обладает высокой бактериостатической и бактерицидной активностью по отношению к клиническим штаммам A. baumannii и P. aeruginosa. В опытных пробирках с экстрактом рост микроорганизмов визуально не обнаружен, что свидетельствует о значительной бактериостатической активности продуктов биодеградации сплава. При изучении бактерицидной активности установлено, что максимальный рост бактерий на агаре отмечен только после первого высева из пробирок (24 ч инкубации экстракта), в которые накануне были добавлены микроорганизмы в концентрации 109, 108, 107 КОЕ/мл. По мере термостатирования количество колоний, вырастающих на агаре после второго высева (48 ч инкубации экстракта), значительно уменьшалось, а после третьего высева (72 ч инкубации экстракта) рост микроорганизмов на плотной среде отсутствовал в большинстве опытов. Высокая бактерицидная активность продуктов биодеградации сплава отмечена в опытах с экстрактом, где к емкостям накануне добавлено 106, 105, 104 КОЕ/мл, – рост колоний на плотной среде после высева из этих пробирок отсутствовал в течение всего эксперимента. Выводы. Продукты биодеградации магниевого сплава МЛ-10 проявляют высокую бактерицидную активность в отношении клинических штаммов неферментирующих грамотрицательных микроорганизмов, а именно по отношению к A. baumannii и P. aeruginosa, являющихся основными возбудителями имплантат-ассоциированных инфекций.
Антибактеріальні властивості модифікованого магнієвого сплаву in vitro щодо клінічних штамів неферментуючих грамнегативних мікроорганізмів
Антибактериальные свойства модифицированного магниевого сплава in vitro по отношению к клиническим штаммам неферментирующих грамотрицательных микроорганизмов
Keywords: magnesium alloy; implant; antibacterial properties; Acinetobacter baumannii; Pseudomonas aeruginosa; імплантат; магниевый сплав; имплантат; антибактериальные свойства